"Queering" Eliza Haywood. - INGRASSIA, CATHERINE (Journal for Early Modern Cultural Studies)
Scholars consistently read the texts of Eliza Haywood through a culturally defined heteronormative lens. Yet Haywood's texts in multiple genres throughout the course of her career structurally and descriptively present same- sex relationships of varying degrees of intimacy. This essay explores what happens when we disrupt our methods for interpreting Haywood and complicate our readings by recognizing her creation of non- normative possibilities for intimacy, gender formation, and narrative structures across the span of her career.